Prevalence of Bandemia in Respiratory Viral Infections: A Pediatric Emergency Room Experience - Noyola, Estela; Noor, Asif; Sweeney, Nicole; Chan, Joshua; Ramesh, Rahul; Calixte, Rose; Krilov, Leonard R. (Frontiers in Pediatrics, 2020)
Objective: The aim of this study was to examine the prevalence of bandemia in confirmed respiratory viral infections in febrile infants and children presenting to the emergency department. Methods: An observational retrospective study from January 1, 2016 through December 31, 2016 was conducted in patients between the ages of ≥ 1 month and ≤ 5 years of age presenting to the emergency room with fever and who had a complete blood cell count performed. Patients were separated into seven groups based on the type of respiratory viral infection. Inclusion criteria strictly counted children with viral infections and absence of clinical and laboratory evidence of a bacterial co-infection. Results: A total of 419 patients had a documented viral infection. A significant proportion of these children were found to have bandemia Children with adenovirus (17 %), Respiratory Syncytial Virus (RSV) (14.9 %), human metapneumovirus (hMPV) (13 %), and parainfluenza virus (7.9%) had the highest prevalence when cutoff for bandemia was set at 10 %. The prevalence increased to 35.3%, 30.9 %, 40.3 %, and 15.8 % for adenovirus, RSV, hMPV, and parainfluenza virus respectively when this cutoff was lowered further to 5%. Conclusion: Band neutrophils are detected frequently in confirmed respiratory viral infections during early stages of infection.